An Endurance-Dominated Exercise Program Improves Maximum Oxygen Consumption, Ground Reaction Forces, and Muscle Activities in Patients With Moderate Diabetic Neuropathy - Jafarnezhadgero, AmirAli; Mamashli, Elahe; Granacher, Urs (Frontiers in Physiology, 2021)
Background The prevalence of diabetes worldwide is predicted to increase from 2.8% in 2000 to 4.4% in 2030. Diabetic neuropathy (DN) is associated with damage to nerve glial cells, their axons, and endothelial cells leading to impaired function and mobility. Objective We aimed to examine the effects of an endurance-dominated exercise program on maximum oxygen consumption (VO2max), ground reaction forces, and muscle activities during walking in patients with moderate DN. Methods Sixty male and female individuals aged 45–65 years with DN were randomly assigned to an intervention (IG, n = 30) or a waiting control (CON, n = 30) group. The research protocol of this study was registered with the Local Clinical Trial Organization (IRCT20200201046326N1). IG conducted an endurance-dominated exercise program including exercises on a bike ergometer and gait therapy. The progressive intervention program lasted 12 weeks with three sessions per week, each 40–55 min. CON received the same treatment as IG after the post-tests. Pre- and post-training, VO2max was tested during a graded exercise test using spiroergometry. In addition, ground reaction forces and lower limbs muscle activities were recorded while walking at a constant speed of ∼1 m/s. Results No statistically significant baseline between group differences was observed for all analyzed variables. Significant group-by-time interactions were found for VO2max (p < 0.001; d = 1.22). The post-hoc test revealed a significant increase in IG (p < 0.001; d = 1.88) but not CON. Significant group-by-time interactions were observed for peak lateral and vertical ground reaction forces during heel contact and peak vertical ground reaction force during push-off (p = 0.001–0.037; d = 0.56–1.53). For IG, post-hoc analyses showed decreases in peak lateral (p < 0.001; d = 1.33) and vertical (p = 0.004; d = 0.55) ground reaction forces during heel contact and increases in peak vertical ground reaction force during push-off (p < 0.001; d = 0.92). In terms of muscle activity, significant group-by-time interactions were found for vastus lateralis and gluteus medius during the loading phase and for vastus medialis during the mid-stance phase, and gastrocnemius medialis during the push-off phase (p = 0.001–0.044; d = 0.54–0.81). Post-hoc tests indicated significant intervention-related increases in vastus lateralis (p = 0.001; d = 1.08) and gluteus medius (p = 0.008; d = 0.67) during the loading phase and vastus medialis activity during mid-stance (p = 0.001; d = 0.86). In addition, post-hoc tests showed decreases in gastrocnemius medialis during the push-off phase in IG only (p < 0.001; d = 1.28). Conclusions This study demonstrated that an endurance-dominated exercise program has the potential to improve VO2max and diabetes-related abnormal gait in patients with DN. The observed decreases in peak vertical ground reaction force during the heel contact of walking could be due to increased vastus lateralis and gluteus medius activities during the loading phase. Accordingly, we recommend to implement endurance-dominated exercise programs in type 2 diabetic patients because it is feasible, safe and effective by improving aerobic capacity and gait characteristics.